PENGEMBANGAN MODUL AJAR KEBUTUHAN DAN KEINGINAN BERBASIS PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI SISWA KELAS IV SD - Andini, Listanti Putri; Rusmawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Developing effective communication abilities represents a fundamental educational objective at the elementary level. Nevertheless, social studies instruction in primary schools frequently maintains a teacher-dominated approach, limiting opportunities for students to cultivate their communicative competencies. This investigation focuses on designing an instructional module centered on the needs and wants concept, utilizing Project-Based Learning (PjBL) methodology to enhance fourth-grade students' communication capabilities. The study employs Research and Development (R&D) methodology, implementing the ADDIE framework encompassing five sequential phases: analysis, design, development, implementation, and evaluation. Twenty-five fourth-grade students from SDN Ngemplak 3 participated as research subjects. Data collection utilized expert validation instruments, communication skills assessment tools, and student feedback questionnaires. Validation outcomes revealed that the developed module achieved a mean score of 3.57 on a four-point scale, classified as "Very Good." Effectiveness testing demonstrated enhancement in students' communication skills, evidenced by the progression from a mean pretest score of 62.40 to a posttest mean of 82.60, yielding an N-Gain coefficient of 0.53 (moderate improvement category). Student responses toward the instructional activities proved favorable. Consequently, the PjBL-based module addressing needs and wants demonstrates both feasibility and effectiveness in advancing elementary students' communication skills. Keywords: project-based learning, needs and wants, communication skills